Answer:
the answer is -33 srry couldn't explain :(
Answer:
u = - ( 9-6w)/2
Step-by-step explanation:
to evaluate for u in the expression -2u+6w=9 is simply to look for a way such that we would express u in terms of w and other variables.
solution
-2u+6w=9
-2u = 9 - 6w
divide both sides by the coefficient of u which is -2
-2u/u = 9 - 6w/-2
u = - ( 9-6w)/2
therefore the value of u when rearranged in the equation -2u+6w=9 is evaluated to be equals to
u = - ( 9-6w)/2
Answer:
x ≈ 3.4 cm
Step-by-step explanation:
Using the sine ratio in the right triangle
sin57° =
=
( multiply both sides by 4 )
4 × sin57° = x , thus
x ≈ 3.4 cm ( to 1 dec. place )
Answer:
The answer is 3.75e+7
Step-by-step explanation: